Effect of Protein and Calcium Microparticle feeding with Lactobacillus acidophilus or Citric Acid on Meat Quality - Rachel Rama Gradhinta; Bambang Sukamto; Istna Mangisah (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2020)
This research aims to determine the effect of administering a combination feed of calcium microparticle protein with Lactobacillus acidophilus or citric acid on fat digestibility and the meat of broiler chicken. The cattle used in this research are 15 days old broiler chickens, amounted in 160 chickens. The study uses complete random design (RAL) with 5 treatments and 4 repeat treatmens (8 chickens each). The treatment applied were as follows: T0 (non-microbial feed (protein 21%)), T1 (non-microparticle feed (18% protein + Lactobacillus acidophilus 1.2 ml (108 CFU/ml)), T2 (non-microparticle feed (18% protein + Citric acid 1.2%), T3 (Microparticle feed (18%) + Lactobacillus acidophilus 1.2 ml (108 CFU/ml)), T4 (microparticle feed (18% protein + Citric acid 1.2%). The observed parameters are the digestibility of fat, fat mass of meat, the percentage of abdominal fat and the increase in body weight. The analyzed data results were variegated and continued using Duncan's multiple range test at a 5% probability. Treatment was given from the age of 15 days to 42 days. The results of the study show that the digestibility of fats that had the treatment of feeding protein and calcium microparticles with the addition of real effect Lactobacillus acidophilus is lower than the T0 and T2 but not unlike the T1 and T4 (P<0.05). The fat mass of meat and abdominal fats in the T4 treatment has a real difference (P<0.05) and at the lowest of the T0, T1 and T2 but different from T3. Higher weight increase in T3 treatment is compared to T1, T2 and T4 but not different from T0. Based on the results of the study it can be concluded that feeding microparticles of protein and calcium with Lactobacillus acidophilus 1.2 ml can decrease fat digestibility and increase weight gain but not in the fat mass of meat and abdominal fat percentage. Keywords : broiler, citric acid, Lactobacillus acidophilus, microparticle.